A novel scoring system for predicting adherent placenta in women with placenta previa. (April 2018) - Tanimura, Kenji; Morizane, Mayumi; Deguchi, Masashi; Ebina, Yasuhiko; Tanaka, Utaru; Ueno, Yoshiko; Kitajima, Kazuhiro; Maeda, Tetsuo; Sugimura, Kazuro; Yamada, Hideto
Abstract: Introduction: Placenta previa (PP) is one of the most significant risk factors for adherent placenta (AP). The aim of this study was to evaluate the diagnostic efficacy of a novel scoring system for predicting AP in pregnant women with PP. Methods: This prospective cohort study enrolled 175 women with PP. The placenta previa with adherent placenta score (PPAP score) is composed of 2 categories: (1) past history of cesarean section (CS), surgical abortion, and/or uterine surgery; and (2) ultrasonography and magnetic resonance imaging findings. Each category is graded as 0, 1, 2, or 4 points, yielding a total score between 0 and 24. When women with PP had PPAP score ≥8, they were considered to be at a high risk for AP and received placement of preoperative internal iliac artery occlusion balloon catheters. If they were found to have AP during CS, they underwent hysterectomy or placenta removal using advanced bipolar with balloon catheter occlusion. The predictive accuracy of PPAP score was evaluated. Results: In total, 23 of the 175 women with PP were diagnosed as having AP, histopathologically or clinically. Twenty-one of 24 women with PPAP score ≥8 had AP, whereas two of 151 women with PPAP score <8 had AP. The scoring system yielded 91.3% sensitivity, 98.0% specificity, 87.5% positive predictive value, and 98.7% negative predictive value for predicting AP in women with PP. Discussion: This prospective study demonstrated that PPAP scoring system may be useful for predicting AP in women with PP. Highlights: The PPAP scoring system yielded high accuracy in predicting placenta previa accreta. There was a positive correlation between the PPAP score and the amount of blood loss. The scoring system may be useful in the management of women with placenta previa.